2017
DOI: 10.1002/jbmr.3361
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Areal Bone Mineral Density From Age Eight to Young Adulthood and Factors Associated With Deviation From Tracking: A 17-Year Prospective Cohort Study

Abstract: We have previously shown that bone mineral density (BMD) tracks strongly from age 8 to 16 years. This study aimed to describe whether this strong tracking continued to age 25 years and describe factors associated with deviation from tracking. Ninety-nine participants were followed from age 8 to 25 years and 197 participants from age 16 to 25 years. Outcomes measured were BMD at the spine, hip, and total body (by dual-energy X-ray absorptiometry [DXA]). Other factors measured were anthropometrics, inhaled corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Breastfeeding at a young age and having lean body mass have been shown to push children into higher BMD quantiles. 4,13 Furthermore, smoking and hormone levels contribute to fracture incidence.…”
Section: Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding at a young age and having lean body mass have been shown to push children into higher BMD quantiles. 4,13 Furthermore, smoking and hormone levels contribute to fracture incidence.…”
Section: Other Factorsmentioning
confidence: 99%
“…With early recognition and appropriate intervention, children are not destined to track within a low-BMD quantile for the remainder of their growth. 13…”
Section: Fracture Risk In Children: Identification Of Modifiable Factorsmentioning
confidence: 99%
“…There is evidence of moderate to high tracking (maintenance of the relative position of an individual within the population distribution over time) of BMD through childhood, puberty and into young adulthood [ 11 , 12 ]. This might partly reflect a genetic tendency as osteoporosis has high heritability and numerous loci associated with BMD have been identified in genome-wide association studies (GWAS) [ 13 ].…”
Section: Modifiable Factors Affecting Bone Health In Childhood and Ad...mentioning
confidence: 99%
“…Childhood and adolescence represent critical phases for bone development, with bone mass typically peaking in late adolescence ( 5 , 6 ). Numerous studies have shown that bone mineral density (BMD) is traceable from childhood to adolescence and into adulthood ( 7 , 8 ). Consequently, bone metabolism during childhood and adolescence plays a vital role in preventing OP in later life ( 9 ).…”
Section: Introductionmentioning
confidence: 99%